Controlled fabrication of luminescent and magnetic nanocomposites. (14th March 2018) - Ma, Yingxin; Zhong, Yucheng; Fan, Jing; Huang, Weiren
Abstract: Luminescent and magnetic multifunctional nanocomposite is in high demand and widely used in many scales, such as drug delivery, bioseparation, chemical/biosensors, and so on. Although lots of strategies have been successfully developed for the demand of multifunctional nanocomposites, it is not easy to prepare multifunctional nanocomposites by using a simple method, and satisfy all kinds of demands simultaneously. In this work, via a facile and versatile method, luminescent nanocrystals and magnetic nanoparticles were successfully synthesized through self-assembly under vigorous stirring and ultrasonic treatment. These multifunctional nanocomposites are not only water stable but also find wide application such as magnetic separation and concentration with a series of moderate speed, multicolor fluorescence at different emission wavelength, high efficiency of the excitation and emission, and so on. By changing different kinds of luminescent nanocrystals and controlling the amount of luminescent and magnetic nanoparticles, a train of multifunctional nanocomposites was successfully fabricated via a versatile and robust method.